Approximation of unbounded operators by bounded operators in a Hilbert space - Bilichenko, R. O.; Babenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We determine the best approximation of an arbitrary power A^k of an unbounded self-adjoint operator A in a Hilbert space H on the class {x ∈ D(A^r ) : ∥A^r x∥ ≤ 1}, k < r.